Prevalência e fatores associados aos sintomas osteomusculares em dentistas do município de Natal - RN - Dantas, Filipe Fernandes Oliveira (2012)
Musculoskeletal disorders are one of the most important occupational health issues related to workers' health, especially among dentists, in which have been found high prevalence of pain in different anatomical regions of the body related to their professional activity. Accordingly, this study aimed to determine the prevalence of musculoskeletal symptoms among dentists, and analyzing this prevalence in different anatomical regions. Additionally, it was checked whether there is an association between the occurrence of symptoms with demographic, anthropometric, occupational habits, lifestyle, ergonomic variables and stressful work environment for dentists of Natal - RN. Therefore, it was applied in 387 dentists of Natal, the Brazilian version of the Nordic Musculoskeletal Questionnaire validated in order to assess the presence of disturbances. Also we used the reduced version of the scale of stress in the workplace, validated for the Brazilian population, and a questionnaire featuring items related to ergonomics in the dentist's office. Initially a descriptive analysis of all data on the dependent and independent variables. Data on the dependent variables (musculoskeletal symptoms of the various anatomical regions) underwent an exploratory factor analysis in order to produce new dependent variables factor. Tire bivariate analysis between the dependent variables and independent variables factor was conducted by chi-square statistical test for significance levei of 5%. Among the main results, we observed a high prevalence of musculoskeletal symptoms (86%). Considering the anatomical regions analyzed, the lumbar region had the highest prevalence of symptoms (58.4%). Regarding the observed associations, the variables related to the physical demands of labor were significantly associated with the occurrence of musculoskeletal symptoms, especially in joints connected to the trunk. Regarding the ergonomic variables, only the inadequacy of ergonomic dental cabinet was significantly associated with pain in the trunk and wrist / hand / fmgers. Now with respect to stressor variables showed that these variables were not associated with the occurrence of musculoskeletal symptoms. Thus, it was considered relevant work lumbar segmentai stabilization, which can be indicated as an altemative non-drug to aid in the prevention and improvement of the main symptoms of pain professionals.